PENGARUH KOMPENSASI, PELATIHAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERIKANAN KOTA TANJUNGBALAI - Muhammad Husin; Desfi Marlisa Nasution; M. Fazlur Rahman Daulay; Novi Afriani; Robert Arozatulo Zebua (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this study is: How does compensation, training and work motivation influence the work productivity at Dinas Perikanan Kota Tanjungbalai. This study aims to determine the effect of compensation, training and work motivation on employee work productivity. With total sampling technique, the sample in this study was 41 people. The results showed; Compensation partially has a positive effect on employee work productivity; Partial training has a positive effect on employee work productivity; Work motivation partially has a positive influence on employee work productivity; Training, compensation and work motivation simultaneously have a positive and significant effect on employee work productivity.